(3GdfXGe GdbGfhfj ddGSJKeGQGJ GdOhdjI HGdefGWb GdMQI GdYQHjI (B:s ((3OQGSI ebGQfI(B) /s - (3YHO GdbGOQ, dWQT Ydj YjSis ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2017)
(3jJfGhd gPG GdcJGH eG jdj SLd JGQjN GdGbJUGO GdOhdj GdGSJKeGQGJ GdOhdjI cXGgQI GbJUGOjI hcJTQjY Ohdj gj XGgQI MOjKI bOe TgGOJg HCf GdefGWb GdMQI ZGHQI aj GdbOe hdcf cdGgeG NOe GdBNQ aj YdGbI GbJUGOjI WQOjI eMdjI hOhdjI eHjfG Cf GdYhdeI GdbGfhfjI ef NdGd bGfhf GdGbJUGO GdOhdj CNQLJ GdefGWb GdMQI ef GdTDhf GdbGfhfjI GdGbJUGOjI GdJfehjI GdOGNdjI ddOhd Edi Jchjf LShQ NGQLjI Hjf GdOhd ef NdGd GdEJaGbjGJ GdOhdjI GdKfGFjI hGdeTJQcI djHQRdgG Qbe LOjO aj JUfjaGJ GdefGWb GdMQI CdG hgj GdefGWb GdMQI GdOhdjI(B.s
(3JUeej GdZdGa (B: (3GdQhGO(B.s
(3HHdjhLQGajI (B: (3UaMI (B557-570.s
Keywords: (3GdGSJKeGQGJ GdCLfHjIs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdefGWb GdMQIs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs; (3GdGSJKeGQ GdOhdjs -- (3bhGfjf hJTQjYGJs -- (3GdHdGO GdYQHjIs